PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TSTS BERBANTUAN LKS TERHADAP HASIL BELAJAR MATERI LAJU REAKSI - Rinarti, Sri Mulyo; Enawaty, Eny; Lestari, Ira (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe purposes of this research are to; (1) determine the differences in learning outcomes between students who taught by TSTS cooperative model assisted with students? worksheet and the students who taught by conventional model; (2) to determine the influence of TSTS cooperative model toward learning outcomes on reaction rate materials. This research is a quasi experimental using nonequivalent control group design. Saturation sampling is the sampling method that will be conducted in this research. Data collecting technique that will be conducted are scaling, observation and interview. While the instrument of the research are learning tests outcomes, observation sheets and interview guidance. Based on statistic data analysis using Mann Whitney U as ? = 0,05, resulting sig score 0,014 < 0,05 which means there is a differences in learning outcomes between students who taught by TSTS cooperative model assisted with students? worksheet and the students who taught by conventional model. The use of TSTS cooperative model of students? worksheet gave influences 24, 22% to the students learning outcomes on reaction rate materials. Keywords: Two Stay Two Stray (TSTS), Students? worksheets, Learning outcomes, Reaction rate